Volumetric modulated arc therapy versus tomotherapy for late T-stage nasopharyngeal carcinoma - Chen, Qian; Tang, Lingwei; Zhu, Zhe; Shen, Liangfang; Li, Shan (Frontiers in Oncology, 2022)
Abstract Purpose: To compare the dosimetric parameters and clinical outcomes between volumetric modulated arc therapy (VMAT) and tomotherapy for treating late T-stage nasopharyngeal carcinoma (NPC). Methods: Patients with non-metastatic late T-stage NPC who received definitive radiotherapy with tomotherapy or VMAT were selected. 1:1 propensity score matching (PSM) was used to control the balance of confounding factors. The dosimetric parameters and clinical outcomes were compared. Results: A total of 171 patients were enrolled before matching, with 61 patients in the VMAT group and 110 patients in the tomotherapy group. In the post-PSM cohort, 54 sub-pairs of 108 patients were included after matching. Tomotherapy was superior to VMAT in the dosimetric parameters of planning target volumes, brainstem, spinal cord, lenses, and parotid glands but inferior in the optic nerves and optic chiasm. The tomotherapy group had a lower incidence of grade ≥ 3 acute mucositis ( 22.2% vs. 40.7%, p = 0.038) and a higher rate of complete response (83.3% vs. 66.7%, p = 0.046) after radiotherapy. However, there were no significant differences in locoregional failure-free survival (p = 0.375), distant metastasis-free survival (p = 0.529), or overall survival (p = 0.975) between the two groups. Conclusion: Tomotherapy is superior to VMAT in terms of most dosimetric parameters, with less acute mucositis and better short-term efficacy. There are no significant differences in the survival outcomes between the VMAT and tomotherapy groups.